What is 'Early intervention' for work related difficulties for people with multiple sclerosis?: a case study report - Sweetland, Joanne; Playford, Diane E.; Radford, Kathryn A. (OMICS International, 2014)
Background: Employment matters and at diagnosis most people with multiple sclerosis are in full time work or education. 75% of people with multiple sclerosis report the condition has impacted on this employment or career opportunities. Early intervention to support people in work is advocated for in the literature. This paper starts the journey of exploring what is meant by early. Methods: A randomized control trial was undertaken offering either occupational therapy led early intervention or usual care to people diagnosed with multiple sclerosis within one year. Two cases were purposively selected from the treatment group and used to illustrate the importance as well as the nature of early intervention. Results: Both participants received occupational therapy led support which included fatigue management, advice about legal rights, support accessing services such as Access to Work, and support with disclosure in the workplace. Conclusions: Neither of the participants had reported any work problems at the point of referral. However the clinical intervention led to the identification of small concerns and worries. The education and support offered to these two participants alleviated these worries. Early support and education to enable people with multiple sclerosis to manage their condition in the work place can have a positive impact. This may equip them better for the journey ahead.